1927
DOI: 10.1037/h0070844
|View full text |Cite
|
Sign up to set email alerts
|

The rôle of practice in speed of association.

Abstract: Proficiency in a given performance is usually measured in terms of the speed and effectiveness with which the task is executed. The results of experiments on learning and practice would seem to indicate that such proficiency is influenced by four factors, each of which may vary independently: (i) the ease with which the individual motor adjustments are carried into effect, (2) the ease with which the elements calling for adjustment are discriminated, (3) the ease with which the recognized sensory elements lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
34
2

Year Published

1966
1966
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 3 publications
8
34
2
Order By: Relevance
“…First, W scanning times were longer than C times (Fs from 79 to 155, ps < .001, within each cell), confirming Lund's (1927) finding (see Fig. I).…”
Section: Preliminary Analysessupporting
confidence: 76%
See 1 more Smart Citation
“…First, W scanning times were longer than C times (Fs from 79 to 155, ps < .001, within each cell), confirming Lund's (1927) finding (see Fig. I).…”
Section: Preliminary Analysessupporting
confidence: 76%
“…Most investigators favor a differential practice explanation [see Jensen & Rohwer's (1966) comprehensive review of the Stroop literature ]. Lund (1927, cited by Jensen & Rohwer, 1966 found that scanning times for colors are shorter than for words. Thus, if Ss scan for red on C, they should do this faster than scanning for RED on W. This is a reversal of the usual relation between times on C and W, when Ss name or read each instance.…”
mentioning
confidence: 99%
“…Cattell, it is known that the time for naming (verbal reaction time) an object (or a color, a geometric figure, a drawing) is longer than the time for reading the name of that object. This result has been conflfmed by Lund (1927), Ligon (1932), Fraisse (1964), but the explanation of this phenomenon is still disputed.…”
Section: Verbal Reaction Time To Drawings Is Always a Little Longer Tmentioning
confidence: 91%
“…Cattell, it is known that the time for naming (verbal reaction time) an object (or a color, a geometric figure, a drawing) is longer than the time for reading the name of that object. This result has been conflfmed by Lund (1927), Ligon (1932), Fraisse (1964, but the explanation of this phenomenon is still disputed.In attempting to explain the difference between the time for naming an object (object-naming) and the time for reading the corresponding name (word-reading), Brown (1915), Ligon (1932), Fraisse (1964) have studied the role of practice. However, it is to be noted that practice reduces but does not suppress the difference.…”
mentioning
confidence: 90%
“…, observing that it takes more time to name colors than to read color llames (Brown, 1915;Lund, 1927;Ligon, 1932), proposed a technique for investigating the interfering effect of the presence of conflicting word stimuli upon naming colors (e.g., the word "blue" is printed on the color red, the task being to name the color of the ink and ignore the word). The series of tasks has proved discriminative in studies attempting to elaborate cognitive styles (Broverman & Lazarus, 1958;Broverman, 1960), in studies comparing groups which are ordered developmentally (Comalli, Wapner, & Werner, 1962;Schiller, 1966), and in Ss under primitivizing drugs vs placebo conditions (Wapner & Krus, 1960).…”
mentioning
confidence: 99%